Effects of Ganodermanondiol, a New Melanogenesis Inhibitor from the Medicinal Mushroom Ganoderma lucidum - Ji-Woong Kim (International Journal of Molecular Sciences, 2016)
Ganoderma lucidum, a species of the Basidiomycetes class, has been attracting international attention owing to its wide variety of biological activities and great potential as an ingredient in skin care cosmetics including “skin-whitening” products. However, there is little information available on its inhibitory effect against tyrosinase activity. Therefore, the objectives of this study were to investigate the chemical composition of G. lucidum and its inhibitory effects on melanogenesis. We isolated the active compound from G. lucidum using ethanol extraction and ethyl acetate fractionation. In addition, we assayed its inhibitory effects on tyrosinase activity and melanin biosynthesis in B16F10 melanoma cells. In this study, we identified a bioactive compound, ganodermanondiol, which inhibits the activity and expression of cellular tyrosinase and the expression of tyrosinase-related protein-1 (TRP-1), TRP-2, and microphthalmia-associated transcription factor (MITF), thereby decreasing melanin production. Furthermore, ganodermanondiol also affected the mitogen-activated protein kinase (MAPK) cascade and cyclic adenosine monophosphate (cAMP)-dependent signaling pathway, which are involved in the melanogenesis of B16F10 melanoma cells. The finding that ganodermanondiol from G. lucidum exerts an inhibitory effect on tyrosinase will contribute to the use of this mushroom in the preparation of skin care products in the future.